Fifth Grade Elementary Science Psychomotor Assessment Instruments - Benedicta Rani Nugraheni; Widihastuti; Edi Istiyono (Universitas Pendidikan Ganesha, 2023)
The lack of variation in the assessment of the psychomotor domain in science learning in elementary schools and the need for appropriate assessment instruments in online practical learning. The study aimed to analyze the quality of the development of the psychomotor assessment instrument for fifth-grade elementary school children on limb material. This type of research is development research. The subjects of this study were 87 students in grade 5 elementary school. Retrieval of data with self-assessment sheets was carried out using the Google form. The questionnaire consists of 10 statement items with four answer choices. Sampling technique with purposive sampling. The criteria used in the decision were: 5th-grade elementary school students who had studied limb material. Content validity was verified using Aiken's V formula and construct validity using EFA. Calculation of instrument reliability using the Alpha Cronbach formula. The results of this study are that the psychomotor domain assessment instrument has valid and reliable instrument criteria. The instrument used has a validity value in the